Antena Multiple Input – Multiple Output (Mimo) Empat Elemen Untuk Teknologi 5G - Maharani, Zhanni (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2023)
Multiple Output (MIMO) antenna is a technology in wireless communication that employs several transmission and reception antennas to enhance performance and communication speed. This MIMO with four elements features a low correlation coefficient and high element isolation, with the goal of enhancing communication performance quality. In this study, a MIMO antenna is designed using CST Studio 2019 software, utilizing an FR-4 Epoxy substrate measuring 40 x 40 mm, with a thickness of 1.6 mm and a dielectric constant of 4.4. Simulation and measurement results demonstrate that the antenna design meets the specified requirements, including a low return loss value of -10 dB, a wide bandwidth of approximately 1700 MHz for simulation, and 1100 MHz for measurement. The mutual coupling value for simulation is <-15 dB, and the mutual coupling result for measurement is <-20 dB. The correlation coefficient values are < 0.1 for simulation and < 0.25 for measurement. Consequently, this antenna holds the capability to support 5Gcommunication applications with good performance quality; however, it requires refinement for further development into an effective solution for enhancing the efficiency of next-generation communication.